ABLATION OF CR2TE3 CRYSTAL BY ND3+:YAG LASER - Wisz, Grzegorz; Barwiński, Michał; Sagan, Piotr; Kuźma, Marian (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2014)
In the paper, the process of laser ablation of Cr2Te3 has been studied in the respect of its application to thin solid films deposition of this material in the pulsed laser deposition (PLD) technology. Target has been prepared in the shape of pressed tablet from powder Cr2Te3 .The energy density of the Nd3+:YAG laser beam were 16 J/cm2 and 34 J/cm2 and the time of laser pulse was 20 ns. The composition of the surface layer of the target after ablation has been measured using EDX method. The excess of chromium in respect to it amount in initial composition has been measured. This result points on the weak desorption of this component at the ablation parameters applied.